The Influence of Adverse Childhood Experiences (ACEs) on the Functional Impairment of Justice-Involved Adolescents: A Comparison of Baseline to Follow-Up Reports of Adversity. (October 2021) - Duron, Jacquelynn F.; Williams-Butler, Abigail; Liu, Feng-Yi Y.; Nesi, Danielle; Fay, Kathleen Pirozzolo; Kim, Bo-Kyung Elizabeth
Adverse childhood experiences (ACEs) have long been recognized for negatively influencing individual outcomes such that each additional ACE exposure increases the risk for negative health and behavioral outcomes. Little is known, however, about how the more recent accumulation of ACEs occurring in follow-up periods influence global functioning considering the past accumulation of ACEs reported at baseline by justice-involved adolescents. Participants were 851 adolescents who completed the Northwestern Juvenile Project (NJP), a longitudinal survey. OLS regression models were used to examine the influence of follow-up and baseline ACEs on the functional impairment of youth. Results indicate that both follow-up and baseline ACEs were associated with worse functioning over time with baseline ACEs demonstrating a greater effect. This study highlights the importance of assessing accumulations of ACEs over time for adolescents in the juvenile justice system and considering how youth of different characteristics and experiences may differently encounter functional impairment. Implications for offering trauma-informed services to disrupt the effects of adversity on adolescents' functioning are discussed.